Sounds of Change: How Podcasting Empowers Managers in Insurance Transformation - Basir, Yulinda (LPPM Stikosa - AWS, 2024)
To navigate the challenging landscape of COVID-19 disruptions and new regulatory demands, life insurers in Indonesia are undertaking strategic initiatives to regain market dominance. A critical aspect of this strategy is the innovation of internal communication methods to foster employee support during organizational changes. This paper presents a qualitative study that explores middle managers’ perceptions and experiences in the insurance industry regarding the use of podcast episodes as an internal communication medium. This study employed in-depth interviews to gain insights into managers' attitudes towards podcasting for internal communication. The findings revealed that Managers perceived podcast episodes as a convenient and engaging tool for information consumption. Furthermore, they believe that podcasts can foster relationships between employees and managers, and provide an effective platform for sharing company news and best practices in an informative and engaging manner. This study underscores the potential of podcast episodes as valuable tools for internal communication in the insurance industry, particularly during the periods of transformation. The results suggest that podcasting can enrich the communication strategies employed during organizational change, thereby aiding the successful realization of transformation objectives. Future research suggestions include exploring the types of content most effectively delivered via podcasts, assessing the long-term impacts of podcast engagement, and investigating the potential challenges and best practices related to implementing podcast channels for internal communication. These research directions can further our understanding of the potential and effectiveness of podcasting as an internal communication tool for the insurance industry.